Menjaga Keabadian atau Memenuhi Kebutuhan? Dilema Penjualan Aset Wakaf dalam Perspektif Fiqih - Ahmad Fauzan Azhima; Irsan Irsan; Aslati Aslati (Yayasan Cendekia Gagayunan Indonesia, 2025)
The productivity of waqf assets is crucial for ensuring their long-term benefits. However, many nazir face limited operational funds for maintenance and development. This situation raises a dilemma: can the partial sale of waqf assets for operational purposes be justified, while the principle of perpetuity in Islamic jurisprudence strictly prohibits the transfer of ownership except in cases of necessity? Previous studies have largely examined istibdal in the form of exchanging unproductive assets, leaving a research gap regarding the sale of waqf assets to sustain institutional operations. This study employs a library research method with a doctrinal legal research approach and comparative fiqh analysis, supplemented by a statutory approach to Indonesian waqf legislation. The data sources consist of classical fiqh texts from the four major schools of thought as well as contemporary literature on Indonesian waqf regulations. The analysis is framed within maqashid al-shariʿah and the principle of necessity. The findings indicate that the sale of waqf assets for operational purposes is fundamentally prohibited for three main reasons: (1) it contradicts the principle of perpetuity; (2) as long as the assets remain beneficial, their sale is impermissible according to the majority of jurists; and (3) alternative solutions exist without resorting to sale. Nevertheless, this issue is not only normative but also has significant implications for national waqf governance. Therefore, collective ijtihād and stronger collaboration between the Indonesian Waqf Board (BWI), the Indonesian Council of Ulama (MUI), and Islamic financial regulators are required to establish technical standards for istibdal.